Total Serum Testosterone and Western Ontario and McMaster Universities Osteoarthritis Index Pain and Function Among Older Men and Women With Severe Knee Osteoarthritis - Freystaetter, Gregor; Fischer, Karina; Orav, Endel J.; Egli, Andreas; Theiler, Robert; Münzer, Thomas; Felson, David T.; Bischoff‐Ferrari, Heike A. (Arthritis care & research (2010), 2020)
Objective To investigate whether serum total testosterone level is associated with knee pain and function in men and women with severe knee osteoarthritis (OA). Methods We enrolled 272 adults age ≥60 years (mean ± SD age 70.4 ± 4.4 years, 53% women) who underwent unilateral total knee replacement (TKR) due to severe knee OA. Serum testosterone levels and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and function of the operated and contralateral knee were measured at 6–8 weeks after surgery. At the nonoperated knee, 56% of participants had radiographic knee OA with a Kellgren/Lawrence grade ≥2. Cross‐sectional analyses were performed by sex and body mass index (BMI) subgroups, using multivariable regression adjusted for age, physical activity, and BMI. Results At the operated knee, higher testosterone levels were associated with less WOMAC pain in men (B = –0.62, P = 0.046) and women (B = –3.79, P = 0.02), and less WOMAC disability scores in women (B = –3.62, P = 0.02) and obese men (B = –1.99, P = 0.02). At the nonoperated knee, testosterone levels were not associated with WOMAC pain in men or women, but higher testosterone levels were associated with less disability in women (B = –0.95, P = 0.02). Testosterone levels were inconsistently associated with pain and disability in BMI subgroups among men. Only among obese women, testosterone levels were inversely associated with radiographic knee OA (odds ratio = 0.10, P = 0.003). Conclusion Higher total testosterone levels were associated with less pain in the operated knee in men and women undergoing TKR and less disability in women. At the nonoperated knee, higher testosterone levels were inconsistently associated with less pain and disability.